FEATURES OF MANGANESE ALLOYING OF WEAR RESISTANT HIGH CHROME CAST IRON - V. V. Netrebko; I. P Volchok (Литьë и металлургия)
The influence of alloying by manganese on the structure and hardness of high-chromium wear-resistant cast iron was investigated.